The use of digital technologies for people with disabilities in post-pandemic public schools (Research, Society and Development, 2023)
The COVID-19 pandemic has brought about numerous changes in educational systems, especially with regard to the use of technologies. One of the challenges for public schools was precisely the use of these technologies, especially with regard to teaching students with special needs. This work, through a literature review, aimed to discuss the use of digital technologies in education aimed at students with special needs after the pandemic period. The integration of Information and Communication Technologies in educational environments favors the awareness, acceptance and understanding of students with disabilities, as well as the training of teachers in software applied to teaching. In this way, it discusses how ICTs help to respond to the special educational needs presented by students with disabilities and, thus, seek to include these technologies in school, resulting in new educational scenarios, new teaching strategies and new ways of learning. Therefore, it is pointed out that the use of ICT in education presents great advantages for the student and for the teacher who fit into didactic strategies and proposals that promote significant contributions for each type of disability. Thus, framing the didactic strategies and proposals for the incorporation of ICT in the classroom within the concept of inclusive education that presupposes the definition of objectives and the search for resources that promote significant contributions for each type of disability and introduce an improvement in educational quality.